Neural Induction with Neurogenin 1 Enhances the Therapeutic Potential of Mesenchymal Stem Cells in an Amyotrophic Lateral Sclerosis Mouse Model. Issue 5 (May 2013) - Choi, Chan-Il; Lee, Young-Don; Kim, Heejaung; Kim, Seung Hyun; Suh-Kim, Haeyoung; Kim, Sung-Soo
Amyotrophic lateral sclerosis (ALS) is characterized by progressive dysfunction and degeneration of motor neurons in the central nervous system (CNS). In the absence of effective drug treatments for ALS, stem cell treatment has emerged as a candidate therapy for this disease. To date, however, there is no consensus protocol that stipulates stem cell types, transplantation timing, or frequency. Using an ALS mouse model carrying a high copy number of a mutant human superoxide dismutase-1 (SOD1) G93A transgene, we investigated the effect of neural induction on the innate therapeutic potential of mesenchymal stem cells (MSCs) in relation to preclinical transplantation parameters. In our study, the expression of monocyte chemoattractant protein-1 (MCP-1) was elevated in the ALS mouse spinal cord. Neural induction of MSCs with neurogenin 1 (Ngn1) upregulated the expression level of the MCP-1 receptor, CCR2, and enhanced the migration activity toward MCP-1 in vitro. Ngn1-expressing MSCs (MSCs-Ngn1) showed a corresponding increase in tropism to the CNS after systemic transplantation in ALS mice. Notably, MSCs-Ngn1 delayed disease onset if transplanted during preonset ages, whereas unprocessed MSCs failed to do so. If transplanted near the onset ages, a single treatment with MSCs-Ngn1 was sufficient to enhance motor functions during the symptomatic period (15–17 weeks), whereas unprocessed MSCs required repeated transplantation to achieve similar levels of motor function improvement. Our data indicate that systemically transplanted MSCs-Ngn1 can migrate to the CNS and exert beneficial effects on host neural cells for an extended period of time through paracrine functions, suggesting a potential benefit of neural induction of transplanted MSCs in long-term treatment of ALS.